1159. Pharmacokinetics, Safety, and Tolerability of Imipenem/Cilastatin/Relebactam in Pediatric Participants With Confirmed or Suspected Gram-negative Bacterial Infections: A Phase 1b, Open-label, Single-Dose Clinical Trial. (4th December 2021) - Bradley, John S; Makieieva, Nataliia; Tøndel, Camilla; Roilides, Emmanuel; Kelly, Matthew S; Patel, Munjal; Vaddady, Pavan; Maniar, Alok; Zhang, Ying; Paschke, Amanda; Butterton, Joan R; Chen, Luke F
Abstract: Background: Imipenem/cilastatin/relebactam (IMI/REL) is approved for treating hospital-acquired/ventilator-associated bacterial pneumonia, complicated urinary tract infection, and complicated intra-abdominal infection in adults. This study assessed single-dose pharmacokinetics (PK), safety, and tolerability of IMI/REL in neonatal and pediatric participants with confirmed or suspected gram-negative bacterial infections. Methods: This was a phase 1, open-label, non-comparative study (NCT03230916). Age- and weight-adjusted dosing is summarized in Table 1. The primary objective was to characterize the PK profiles for imipenem and relebactam after a single intravenous dose of IMI/REL. PK parameters were analyzed using population modeling. The PK target for imipenem was the percent time of the dosing interval that the unbound plasma concentration exceeded the minimum inhibitory concentration (%fT >MIC) of ≥30% (MIC used, 2 µg/mL). The PK target for relebactam was an area under the curve (AUC)/MIC ratio >8 (MIC used, 2 µg/mL), corresponding to AUC0-24h >58.88 μM∙h. Safety and tolerability were assessed for up to 14 days after drug infusion. Results: Of the 46 participants who received IMI/REL, 42 were included in the PK analysis. The mean plasma concentration-time profiles for imipenem and relebactam were generally comparable across age cohorts (Figure). For imipenem, the geometric mean %ƒT >MIC ranged from 50% to 94% and the mean maximum concentration (Cmax ) ranged from 65 μM to 126 μM (Table 2). For relebactam, the geometric Cmax ranged from 33 μM to 87 μM and mean AUC0-6h ranged from 51 μM·h to 159 μM·h across the age cohorts (Table 2). IMI/REL was well tolerated with 8 (17.4%) participants experiencing ≥1 adverse events (AE) and 2 (4.3%) participants experiencing AE that were deemed drug related by the investigator. Drug-related AE were increased alanine aminotransferase, increased aspartate aminotransferase, anemia, and diarrhea, which were non-serious, mild in severity, and resolved within the follow-up period of 14 days. Figure 1 Conclusion: Imipenem and relebactam exceeded the pediatric plasma PK targets across pediatric age cohorts in the study; the single doses of IMI/REL were well tolerated. These results will inform IMI/REL dose selection for further pediatric clinical evaluation. Disclosures: Camilla Tøndel, MD, PhD, Merck & Co., Inc., (Grant/Research Support) Emmanuel Roilides, MD, PhD, FIDSA, FAAM, FESCMID, FECMM, FISAC, Merck Sharp & Dohme Corp. (Consultant, Grant/Research Support) Matthew S. Kelly, MD, MPH, Merck Sharp & Dohme Corp. (Consultant, Grant/Research Support) Munjal Patel, PhD, Merck Sharp & Dohme Corp. (Employee, Shareholder) Pavan Vaddady, PhD, Merck Sharp & Dohme Corp. (Employee) Alok Maniar, MD, MPH, Merck Sharp & Dohme Corp. (Employee, Shareholder) Ying Zhang, PhD, Merck & Co., Inc. (Employee, Shareholder) Amanda Paschke, MD MSCE, Merck Sharp & Dohme Corp. (Employee, Shareholder) Joan R. Butterton, MD, Merck Sharp & Dohme Corp. (Employee, Shareholder) Luke F. Chen, MBBS MPH MBA FRACP FSHEA FIDSA, Merck (Employee)